Peranan tradisi tonotwiyat suku adat Enggros - Tobati dalam menunjang konservasi hutan mangrove teluk Youtefa: Studi literatur - Amalia Putri Salsabila; Hertien Koosbandiah Soertikanti (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The mangrove forest in Youtefa Bay, Jayapura, Indonesia, has a central role in maintaining the balance of the ecosystem and the lives of local communities. In general, it is known that the physical function of mangrove forests is as a wave absorber, coastal protector, fisheries habitat and neutralizer of water pollution. Mangrove areas, especially in Youtefa Bay, Jayapura City, have experienced a reduction in area of 278.12 Ha from 1967 to 2017 due to residential and infrastructure development. The Tonotwiyat or Women's Forest tradition, implemented by the Enggros and Tobati Indigenous Tribes, shows the important role of local communities in preserving mangrove forests. This system regulates the division of foraging areas between men and women, maintains natural balance, and ensures the sustainability of natural resources. The method used in compiling this article is the literature review method to dig up information from various sources, with a focus on cultural, social aspects, spiritual values and the positive impact of the Tonotwiyat tradition. This research uses secondary data in the form of books, encyclopedias and scientific journals which can be accessed on the Google Scholar page. The data analysis method used is descriptive analysis. The results of this research describe the worrying condition of the Youtefa Bay mangrove forest, especially because it is affected by the transition to tourist areas and development. The Tonotwiyat tradition plays a key role in preserving mangrove forests. Even though the Youtefa Bay mangrove forest area is experiencing degradation, the awareness of indigenous peoples, especially indigenous women, who consider mangrove forests to have sacred value has encouraged them to rehabilitate and replant mangroves. The Tonotwiyat tradition not only protects indigenous women, but also maintains the sustainability of the surrounding ecosystem. A balance between local traditions and ecosystem conservation is the key to maintaining the sustainability of mangrove forests in Youtefa Bay.